Choosing the mode of transport: Case study of Bratislava region - Daniel Dujava; Richard Kaliés (University of Economics in Bratislava, Department of Economic Policy, 2019)
We analyse commuting patterns in Bratislava's fast growing sub-urban region with suboptimal developed infrastructure. Standardized discrete choice model is used to estimate demand for individual car transport as well as for public buses and trains and to obtain corresponding elasticities with respect to travel costs, times and income. We find low rate of substitution between available modes. Direct price elasticity for public modes is in accordance with often cited rule of thumb -0.3. Negative income elasticities of demand for buses and trains, together with low direct price elasticity for car transport can be hard to overcome when looking for solution of current traffic problems in the region. We use modelled demand to predict effects of two recently proposed policies - new parking system in Bratislava city and construction of highway D4R7. In case of first policy, we expect massive reduction in car usage due to increased costs for car commuters. On the other hand, new highway would have only limited impact on mode choice and could reduce number of train commuters.
Keywords: R41; R42; R48; 330; Elasticities; Mode-choice; Nested Logit Model; Transportation